1981
DOI: 10.1002/jsfa.2740320510
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid composition and characteristics of the kernel fat of different mango (Mangifera indica) varieties

Abstract: The kernels of 13 different mango varieties were examined. The kernels contained, depending on variety, from 6.8 to 12.6 % fat, 5.2 to 6.3 % protein (N x 6.25) and 1.4 to 2.0% ash on a moisture-free basis. The fat was yellow-coloured and melted at 32.5-35.8"C. Stearic and oleic acids constitute about 85% of the total fatty acids.The ratio of stearic:oleic acids varied according to variety from 0.56 to 0.97. The remaining fatty acids are, in decreasing order, palmitic, linoleic, arachidic and linolenic acids. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 5 publications
5
15
1
Order By: Relevance
“…The phospholipids on the basis of fat of MSKP were found to be 2.4%. These values are in close conformity to those reported by Vanpee et al 26 for Gholek variety. The value of total phenolics is considerably lower than that reported by Das and Banerjee.…”
Section: Resultssupporting
confidence: 94%
“…The phospholipids on the basis of fat of MSKP were found to be 2.4%. These values are in close conformity to those reported by Vanpee et al 26 for Gholek variety. The value of total phenolics is considerably lower than that reported by Das and Banerjee.…”
Section: Resultssupporting
confidence: 94%
“…The highest value of 11.14 %, was found in Biantao variety. Similar values were also reported in India (3.7-12.6 %), Zaire (6.8-12.6 %), Bangladesh (7.1-10.0 %) and Kenya varieties (8.5-10.4 %) [1,3,9,25]. About 0.02-0.05 million tons of potential MKF could be extracted annually according to the fat content summarized in Table 1.…”
Section: Mango Varieties and Mango Kernel Fat Contentssupporting
confidence: 80%
“…Table 2 shows the IV and SMP for the 11 kinds of MKF. The IV ranged from 42.20-60.65 g/100 g and were comparable to some other varieties cultivated in Kenya (51.08-51.79 g/100 g), Egypt (50.95-55.35 g/100 g), Bangladesh (44.00-55.00 g/100 g) and Zaire (46.60-57.00 g/100 g) [1,8,9,25]. IV is in relation to the unsaturation of lipids, a higher value indicates a higher content of unsaturated fatty acids and usually reflects the lower SMP value due to such low-melting fatty acids.…”
Section: Mango Varieties and Mango Kernel Fat Contentssupporting
confidence: 70%
“…Van Pee et al (1981) found that the triglyceride composition of the MKS shows a FA distribution in the glycerol molecule characterized by the location of the saturated FA in the sn-1 and sn-3 positions, the remaining sites being proportionately occupied by unsaturated oleic, linoleic, and linolenic acids. In 10 varieties grown in Zaire, MKF oleic and linoleic acids occupied between 85.2 and 89.9%, and 8.3 to 13.0%, respectively, of the sn-2 position in TG molecules.…”
Section: Mango Kernel Fat Compositionmentioning
confidence: 99%